Acquired temozolomide resistance in human glioblastoma cell line U251 is caused by mismatch repair deficiency and can be overcome by lomustine - Stritzelberger, Jenny; Distel, Luitpold; Buslei, R.; Fietkau, Rainer; Putz, Florian (Clinical & Translational Oncology, 2018)
PURPOSE: Glioblastoma multiforme (GBM) is the most common malignant primary brain tumor in adults. While the alkylating agent temozolomide (TMZ) has prolonged overall survival, resistance evolution represents an important clinical problem. Therefore, we studied the effectiveness of radiotherapy and CCNU in an in vitro model of acquired TMZ resistance. METHODS: We studied the MGMT-methylated GBM cell line U251 and its in vitro derived TMZ-resistant subline, U251/TMZ-R. Cytotoxicity of TMZ, CCNU, and radiation was tested. Both cell lines were analyzed for MGMT promotor status and expression of mismatch repair genes (MMR). The influence of MMR inhibition by cadmium chloride (CdCl2) on the effects of both drugs was evaluated. RESULTS: During the resistance evolution process in vitro, U251/TMZ-R developed MMR deficiency, but MGMT status did not change. U251/TMZ-R cells were more resistant to TMZ than parental U251 cells (cell viability: 92.0% in U251/TMZ-R/69.2% in U251; p = 0.032) yet more sensitive to CCNU (56.4%/80.8%; p = 0.023). The effectiveness of radiotherapy was not reduced in the TMZ-resistant cell line. Combination of CCNU and TMZ showed promising results for both cell lines and overcame resistance. CdCl2-induced MMR deficiency increased cytotoxicity of CCNU. CONCLUSION: Our results confirm MMR deficiency as a crucial process for resistance evolution to TMZ. MMR-deficient TMZ-resistant GBM cells were particularly sensitive to CCNU and to combined CCNU/TMZ. Effectiveness of radiotherapy was preserved in TMZ-resistant cells. Consequently, CCNU might be preferentially considered as a treatment option for recurrent MGMT-methylated GBM and may even be suitable for prevention of resistance evolution in primary treatment.
EVALuna2:34594

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

Antiseizure medication and perceived “fair” cost allocation: A factorial survey among neurologists, persons with epilepsy, their relatives, and a control group - Stritzelberger, Jenny; Walther, Katrin; Olmes, David; Gollwitzer, Stefanie; Graf, Wolfgang; Welte, Tamara; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Kriwy, Peter; Hamer, Hajo (Epilepsia, 2022)
Objective: Because resources are limited in modern health care systems, the decision on the allocation of expensive drugs can be supported by a public consent. This study examines how various factors influence subjectively perceived “fair” pricing of antiseizure medication (ASM) among four groups including physicians, persons with epilepsy (PWEs), their relatives, and a control group. Methods: We conducted a factorial survey. Vignettes featured a fictional PWE receiving a fictional ASM. The characteristics of the fictional PWE, ASM, and epilepsy varied. Participants were asked to assess the subjectively appropriate annual cost of ASM treatment per year for each scenario. Results: Fifty-seven PWEs (mean age (SD) 37.7 ± 12.3, 45.6% female), 44 relatives (age 48.4 ± 15.7, 51.1% female), 46 neurologists (age 37.1 ± 9.6, 65.2% female), and 47 persons in the control group (age 31.2 ± 11.2, 68.1% female) completed the questionnaire. The amount of money that respondents were willing to spend for ASM treatment was higher than currently needed in Germany and increased with disease severity among all groups. All groups except for PWEs accepted higher costs of a drug with better seizure control. Physicians and the control group, but not PWEs and their relatives, tended to do so also for minor or no side effects. Physicians reduced the costs for unemployed patients and the control group spent less money for older patients. Significance: ASM effectiveness appears to justify higher costs. However, the control group attributed less money to older PWEs and physicians allocated fewer drug costs to unemployed PWEs.
CRIS-Team Scopus Importer:2022-08-19

Anti-seizure medication is not associated with an increased risk to develop cancer in epilepsy patients - Stritzelberger, Jenny; Lang, Johannes; Mueller, Tamara M.; Reindl, Caroline; Westermayer, Vivien; Kostev, Karel; Hamer, Hajo (Journal of Neurology, 2021)
Objective: Whether anti-seizure medication (ASM) increases the risk for cancer has been debated for decades. While for some ASM, a carcinoma-promoting effect has been suspected, carcinoma-protective effects have been shown for other ASM. However, the issue remains unresolved as data from preclinical and clinical studies have been inconsistent and contradictory. Methods: We collected anonymous patient data from practice neurologists throughout Germany between 2009 and 2018 using the IMS Disease Analyzer database (QuintilesIMS, Frankfurt, Germany). People with epilepsy (PWE) with an initial cancer diagnosis and antiepileptic therapy prior to the index date were 1:1 matched with a control group of PWE without cancer according to age, gender, index year, Charlson Comorbidity Index, and treating physician. For both groups, the risk to develop cancer under treatment with different ASMs was analyzed using three different models (ever use vs. never use (I), effect per one (II) and per five therapy years (III). Results: A total of 3152 PWE were included (each group, n = 1,576; age = 67.3 ± 14.0 years). The risk to develop cancer was not significantly elevated for any ASM. Carbamazepine was associated with a decreased cancer risk (OR Model I: 0.699, p <.0001, OR Model II: 0.952, p =.4878, OR Model III: 0.758, p <.0004). Significance: Our findings suggest that ASM use does not increase the risk of cancer in epilepsy patients.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiseizure medication; Carbamazepine; Carcinogenicity; Epilepsy

Association of interictal epileptiform discharges and serum concentration of levetiracetam and lamotrigine - Lang, Johannes; Willno, Alexander; Reindl, Caroline; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Walther, Katrin; Hamer, Hajo (Frontiers in Neurology, 2024)
Background: Interictal epileptiform discharges (IEDs) are an electrographic biomarker of epilepsy. Despite their crucial role in diagnosing epilepsy, heterogeneous findings exist on the mechanisms underlying their occurrence and the effects of anti-seizure medications (ASMs) on IEDs. Methods: We conducted a study to investigate the association between IED frequency and the serum concentration of two commonly used ASMs, levetiracetam (LEV) and lamotrigine (LTG). We included 56 patients undergoing a continuous video EEG monitoring in our center with tapering of ASM. IED frequency was analyzed using automated and semiautomated methods and serum samples were collected sequentially throughout the stay. Results: The cohort consisted of 41 patients (23 female, 18 male), between 19 and 64 years (mean 37.42 years), most of which were diagnosed with focal epilepsy (93%). IED frequency increased after ASM reduction revealing a negative correlation similarly with LEV and LTG serum concentrations (p = 0.0057 and p = 0.0426, respectively). Discussion: Notably, we observed a significant increase in IED frequency following dose reduction or discontinuation of both medications. This effect was reversed after ASM were re-dosed. This may indicate the suppressive properties of LEV and LTG against epileptic seizures. Furthermore, our study highlights the importance of ASM discontinuation, which may be required for capturing IEDs during diagnostic continuous EEG monitoring, and not be fully explained by circadian or ultradian rhythms alone. Conclusion: Our findings contribute to the understanding of ASM effects on IED frequency dynamics and suggest seizure suppressive properties of LEV and LTG.
CRIS-Team Scopus Importer:2025-04-01
Keywords: anti-seizure medication; anticonvulsants; antiepileptic drugs; interictal epileptiform discharges; spikes

Attitudes toward persons with epilepsy as friends: Results of a factorial survey - Walther, Katrin; Kriwy, Peter; Stritzelberger, Jenny; Graf, Wolfgang; Gollwitzer, Stefanie; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Welte, Tamara; Hamer, Hajo (Epilepsia, 2023)
Objective: Discrimination against persons with epilepsy (PWEs) may persist. The aim of this study was to examine whether epilepsy is an obstacle to desired friendship.Methods: A factorial survey (vignettes), which is less biased by social desirability, was applied to PWEs, their relatives, and lay persons. The vignettes described a person who was varied by the dimensions of age (younger, same age, older), gender (male, female), disease (healthy, mild epilepsy, severe epilepsy [generalized toni-clonic seizures], diabetes), origin (German, non-German), contact (phone/internet, activities at home, activities outside), frequency of contacts (weekly, monthly), and distance (around the corner, 10 km away). Respondents rated their willingness to befriend the person on a 10-point Likert scale. Multivariate regression determined the contribution of each dimension on the judgment.Results: Participants were 64 PWEs (age = 37.1 +/- 14.0 years), 64 relatives of PWEs (age = 45.1 +/- 13.6 years), and 98 controls without contact with PWEs (age = 24.4 +/- 10.1 years). Controls were less interested in a friendship with a PWE with mild epilepsy (-3.4%) and even more avoided PWEs with severe epilepsy (-11.7%), whereas in PWEs with toni-clonic seizures, a mild form of epilepsy was actually conducive to friendship (+7.0%). Controls preferred females (+5.0%) and disliked younger people (-12.3%) and contacts via the internet or telephone (-7.3%). PWEs were also less interested in younger people (-5.8%), and relatives of PWEs had a lower preference for friendships with longer distance (-2.3%).Significance: PWEs still suffer from a risk of social avoidance, and this becomes more evident with generalized motor seizures.
CRIS-Team WoS Importer:2023-02-03

Case report: Cerebrospinal fluid neutrophilic pleocytosis upon intrathecal triamcinolone injection - Tsaktanis, Thanos; Stritzelberger, Jenny; To, Vi Tuong Daniel; Uhl, Martin; Schwab, Stefan; Heuß, Dieter Felix; Rothhammer, Veit (Frontiers in Neurology, 2024)
Intrathecal corticosteroids, initially employed in the 1950s, faced declining use due to complications like arachnoiditis and aseptic meningitis. Triamcinolone, which is nowadays used as intrathecally applied glucocorticoid formulation, has been shown to beneficially influence spasticity without demonstrable influence on disease activity or progression. We here present the case of a patient with recurrent episodes of aseptic cerebrospinal fluid (CSF) neutrophilic pleocytosis over a year following intrathecal triamcinolone treatment. CSF analyses revealed a post-injection CSF cytokine profile resembling cytokine release reaction rather than drug hypersensitivity. This case thus highlights a potential side effect of intrathecal triamcinolone injection with yet unclear clinical relevance, underscores the need for further assessment of clinical benefits of intrathecal triamcinolone, and emphasizes potential short and long-term side effects associated with extended intrathecal triamcinolone use.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemical meningitis; inflammatory CSF syndrome; intrathecal injection of triamcinolone; side effect; spasticity; triamcinolone

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Effect of the AMPA Receptor Inhibitor Perampanel in Combination Therapy with ionizing Radiation on Glioblastoma Cells and Fibroblasts - Knabe, A.; Stritzelberger, Jenny; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Evaluation of simplified wireless EEG recordings in the neurological emergency room - Welte, Tamara; Janner, Felix; Lindner, Sara; Gollwitzer, Stephanie; Stritzelberger, Jenny; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (PLoS ONE, 2024)
Objective In the neurological emergency room (nER), timely electroencephalography (EEG) diagnostic is often crucial in patients with altered state of consciousness as well as in patients presenting with a first seizure. Yet, routine-EEG (rEEG) is often not available, especially during off-hours. Methods We analyzed the value of a commercially available, simplified wireless eight-channel EEG recording (swEEG, CerebAir® EEG headset, Nihon Kohden), applied by non-EEG-specialized medical students, in patients presenting in our nER with (suspicion of) epileptic seizures and/or loss of or altered state of consciousness between 08/2019 and 08/2022. We evaluated the feasibility and validity compared to a standard rEEG (21 electrodes according to the international 10/20 system) and also included the clinical follow-up of the patients. Results 100 patients were included in our analysis (mean age 57.6 ± 20.4 years; 61 male). Median time of electrode application was 7 minutes (range 4–20 minutes), with significantly longer duration in patients with altered level of consciousness (median 8 minutes, p = 0.035). Electrode impedances also differed according to state of consciousness (p = 0.032), and were higher in females (p<0.001). 55 patients received additional rEEG, either during their acute nER stay (25) and/or during the next days (38). Considering normal EEG findings vs. pathological slowing vs. epileptiform activity, swEEG matched first rEEG results in 48/55 cases (87.3%). Overall, swEEG detected the same or additional pathological EEG patterns in 52/ 55 cases (94.5%). In 7/75 patients (9.3%) who did not receive rEEG, or had their rEEG scheduled to a later time point during their hospital stay, swEEG revealed important additional pathological findings (e.g. status epilepticus, interictal epileptiform discharges), which would have triggered acute therapeutic consequences or led to further diagnostics and investigations. Conclusion The introduced swEEG represents a practicable, valuable technique to be quickly applied by non-EEG-specialized ER staff to initiate timely diagnostic and guide further investigations and treatment in the nER. Moreover, it may help to avoid under-diagnostic with potentially harmful consequences caused by skipped or postponed regular 10/20 EEG examinations, and ultimately improve the outcome of patients.
CRIS-Team Scopus Importer:2024-11-15

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

Manufacturer switch of anti-seizure drugs may not increase the risk of seizure recurrence in Children: A nationwide study of prescription data in Germany - Lang, Johannes; Kostev, Karel; Reindl, Caroline; Müller, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Westermayer, Vivien; Trollmann, Regina; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: Several publications on the exchangeability of antiepileptic drugs in clinical settings revealed an increased risk for seizure recurrence after changing the manufacturer of anti-seizure drugs (ASD) in adults, possibly due to a decline of adherence. It is unclear whether this holds true in children and adolescents. Methods: Patient data of children and adolescents (<18 years) were collected anonymously from 236 German pediatricians and pediatric neurologists between January 2011 and December 2018 using the IMS® Disease Analyzer database (IQVIA, Frankfurt, Germany). Patients with epilepsy were included if at least 2 prescriptions within 360 days and 1 within 180 days prior to the index date were available. The cohort was separated into a seizure group and seizure-free controls. Both groups were matched 1:1 according to age, gender, insurance status, and treating pediatrician. The risk for seizure recurrence after a manufacturer switch of the same ASD at the last prescription before the index date was analyzed using a multivariate regression model. Results: A total of 678 children and adolescents with epilepsy were included (each group: n = 339; age: 9.6 ± 4.4 years). Comparing both groups, the risk for seizures recurrence was not increased after a manufacturer switch had occurred. Albeit changes during the last prescription before the index date had occurred more often in the seizure-free group, neither change of branded and generic products nor substances reached significance. Only change of ASD strength showed a significantly reduced odds ratio for seizures (OR 0.40, 95% CI 0.24–0.65, p < 0.001). Significance: In contrast to the available evidence in adults, changing the manufacturer did not appear to increase the risk for seizure recurrence in previously seizure-free children and adolescents with epilepsy.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Anti-seizure drugs; Manufacturer changes; Relapse seizures

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

Radiosensitivity in individuals with tuberous sclerosis complex - Kuhlmann, Lukas; Stritzelberger, Jenny; Fietkau, Rainer; Distel, Luitpold; Hamer, Hajo (Discover Oncology, 2024)
Benign tumors, but rarely cancer, are common in patients with tuberous sclerosis complex (TSC). Blood samples from patients undergoing treatment for TSC at our institution were analyzed for their individual sensitivity to ionizing radiation. Blood samples were collected from 13 adult patients with TSC. The samples were irradiated ex vivo and analyzed by 3-color fluorescence in situ hybridization. In each patient, aberrations were analyzed in 200 metaphases of chromosomes 1, 2, and 4 and scored as breaks. Radiosensitivity was determined by mean breaks per metaphase (B/M) and compared to both healthy donors and oncologic patients. The radiosensitivity (B/M) of the TSC patient cohort (n = 13; female: 46.2%, B/M: 0.48 ± 0.11) was clearly increased compared to healthy individuals of similar age (n = 90; female: 54.4%; B/M: 0.40 ± 0.09; p = 0.001). There was no difference compared to age-matched oncological patients (n = 78; female: 67.9%; B/M 0.49 ± 0.14; p = 0.246). Similarly, the proportion of radiosensitive (B/M > 0.5) and distinctly radiosensitive individuals (B/M > 0.6) was increased in the TSC and oncological patient cohorts (TSC: 30.8% and 7.7%, oncological patients: 46.2% and 14.1%) compared to the healthy individuals (11.1% and 2.2%). Although patients with TSC develop mostly benign and rarely malignant tumors, they are similarly sensitive to radiation as patients with malignant tumors.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Chromosomal aberrations; In situ hybridization; Ionizing radiation; Radiosensitivity; TSC1; TSC2; Tuberous sclerosis complex

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Temozolomide resistance in human glioblastoma cell line U251 is caused by mismatch repair deficiency and can be overcome by lomustine - Stritzelberger, Jenny; Distel, T.; Fietkau, Rainer; Putz, Florian (2016)
EVALuna2:18332

The course of tumor-related epilepsy in glioblastoma patients: A retrospective analysis - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Uhl, Martin; Brandner, Sebastian; Welte, Tamara; Schembs, Leah; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsy and Behavior, 2024)
Purpose: Many patients with glioblastoma suffer from tumor-related seizures. However, there is limited data on the characteristics of tumor-related epilepsy achieving seizure freedom. The aim of this study was to characterize the course of epilepsy in patients with glioblastoma and the factors that influence it. Methods: We retrospectively analyzed the medical records of glioblastoma patients treated at the University Hospital Erlangen between 01/2006 and 01/2020. Results: In the final cohort of patients with glioblastoma (n = 520), 292 patients (56.2 %) suffered from tumor-related epilepsy (persons with epilepsy, PWE). Levetiracetam was the most commonly used first-line antiseizure medication (n = 245, 83.9 % of PWE). The onset of epilepsy was preoperative in 154/292 patients (52.7 %). 136 PWE (46.6 %) experienced only one single seizure while 27/292 PWE (9.2 %) developed drug-resistant epilepsy. Status epilepticus occurred in 48/292 patients (16.4 %). Early postoperative onset (within 30 days of surgery) of epilepsy and total gross resection (compared with debulking) were independently associated with a lower risk of further seizures. We did not detect dose-dependent pro- or antiseizure effects of radiochemotherapy. Conclusion: Tumor-related epilepsy occurred in more than 50% of our cohort, but drug-resistant epilepsy developed in less than 10% of cases. Epilepsy usually started before tumor surgery.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Glioblastoma; Radiochemotherapy; Surgery; Tumor-related epilepsy

The impact of the coronavirus disease (COVID-19) pandemic on outpatient epilepsy care: An analysis of physician practices in Germany - Müller, Tamara; Kostev, Karel; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Westermayer, Vivien; Reindl, Caroline; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: To gain insight into epilepsy care during coronavirus disease (COVID-19) pandemic, we analyzed prescription data of a large cohort of persons with epilepsy (PWE) during lockdown in Germany. Methods: Information was obtained from the Disease Analyzer database, which collects anonymous demographic and medical data from practice computer systems of general practitioners (GP) and neurologists (NL) throughout Germany. We retrospectively compared prescription data for anti-seizure medication (ASM) and physicians’ notes of “known” and “new” PWE from January 2020 until May 2020 with the corresponding months in the three preceding years 2017–2019. Adherence was estimated by calculating the proportion of patients with follow-up prescriptions within 90 days after initial prescriptions in January or February. We additionally analyzed hospital referrals of PWE. The significance level was set to 0.01 to adjust for multiple comparisons. Results: A total of 52,844 PWE were included. Anti-seizure medication prescriptions for known PWE increased in March 2020 (GP + 36%, NL + 29%; P < 0.01). By contrast, a decrease in prescriptions to known and new PWE was observed in April and significantly in May 2020 ranging from −16% to −29% (P < 0.01). The proportion of PWE receiving follow-up prescriptions was slightly higher in 2020 (73.5%) than in 2017–2019 (70.7%, P = 0.001). General practitioners and NL referred fewer PWE to hospitals in March 2020 (GP: −30%, P < 0.01; NL: −12%), April 2020 (GP: −29%, P < 0.01; NL: −37%), and May 2020 (GP: −24%, P < 0.01; NL: −16%). Conclusion: Adherence of known PWE to ASM treatment appeared to remain stable during lockdown in Germany. However, this study revealed findings which point to reduced care for newly diagnosed PWE as well as fewer hospital admissions. These elements may warrant consideration during future lockdown situations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Anti-seizure drugs; COVID-19; Epilepsy care

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Trends in the neurological emergency room, focusing on persons with seizures - Welte, Tamara; Ernst, Sebastian; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (European Journal of Neurology, 2023)
Background and purpose: Previous studies in neurological emergency rooms (nERs) have reported many non-acute, self-presenting patients, patients with delayed presentation of stroke, and frequent visits of persons with seizures (PWS). The aim of this study was to evaluate trends during the last decade, with special focus on PWS. Methods: We retrospectively analyzed patients who presented to our specialized nER during the course of 5 months in 2017 and 2019, and included information on admission/referral, hospitalization, discharge diagnosis, and diagnostic tests/treatment in the nER. Results: A total of 2791 patients (46.6% male, mean age 57 ± 21 years) were included. The most common diagnoses were cerebrovascular events (26.3%), headache (14.1%), and seizures (10.5%). Most patients presented with symptoms lasting >48 h (41.3%). The PWS group included the largest proportion of patients presenting within 4.5 h of symptom onset (171/293, 58.4%), whereas only 37.1% of stroke patients presented within this time frame (273/735). Self-presentation was the most common admission pathway (31.1%), followed by emergency service referral (30.4%, including the majority of PWS: 197/293, 67.2%). Despite known diagnosis of epilepsy in 49.2%, PWS more often underwent accessory diagnostic testing including cerebral imaging, compared to the overall cohort (accessory diagnostics 93.9% vs. 85.4%; cerebral imaging 70.1% vs. 64.1%). Electroencephalography in the nER was only performed in 20/111 patients (18.0%) with a first seizure. Nearly half of the patients (46.7%) were discharged home after nER work-up, including most self-presenters (632/869, 72.7%) and headache patients (377/393, 88.3%), as well as 37.2% (109/293) of PWS. Conclusion: After 10 years, nER overuse remains a problem. Stroke patients still do not present early enough, whereas PWS, even those with known epilepsy, often seek acute and extensive assessment, indicating gaps in pre-hospital management and possible over-assessment.
CRIS-Team Scopus Importer:2023-09-15
Keywords: epilepsy; headache; neurological emergency room; seizures; stroke